Evaluation of Kidney Transplant Recipient in a d Developing Country: Access to the Waiting List. (July 2018) - Ureña, Maria; Taylor, Fabian; Frapiccini, Gabriela; Petrone, Hugo
Abstract : Background: The selection of candidates for kidney transplantation remains a challenge due to complex medical and social situations. There is a progressive increase in the numbers of patients with request for replacement of the renal function and indication of evaluation for kidney transplantation, which is not consonant with the increase in the amount of registered on the waiting list for transplantation, without the information of the causes that generated this difference. Methods: To determine the effectiveness of the renal transplant recipient evaluation (registration in waiting list) and the causes of exclusion for access to waiting list we retrospectively reviewed patients with indication of evaluation for renal transplantation in the period January/10 to October/2017 (202 months). The study group included indications of renal transplant evaluation by the referent nephrologists on the period of study (n= 3207). Results: Nearly 40 % of patients have 2 or more indications. The study included patients in the following categories: no prereferral information (n= 8) 0, 2%; changing of implant center (n= 129) 4 %; refusal to kidney transplant (n= 56) 1, 74%; in assessment (n= 389) 12 %; evaluation exclusion (n= 652) 20, 33 %; suitable for registration (n= 657) 20 %. The group included on waiting list (n= 657): 45, 9 % female (n=302) and 54, 1% male (n=355); 61 % (n=406) complete the evaluation in one indication, 29, 3% (n=193) needs 2 indications and 8, 8% (n=56) needs mora than 3 (3 to six). Conclusion: Only 20% of the indications for evaluations conclude de process of registration on the waiting list. Actions were taken as the realization of clinical interviews and sequential follow-up studies to optimize the resources, to improve the information to the patients and compliance to evaluation.